Future Population Aging in Bangladesh: Economic and Social Aspects (International Journal of Statistical Sciences, 2024)
Recently, Bangladesh has entered into a lower-middle-income country and faces various challenges like other developed countries of the world regarding its population. Eventually, aging will become a challenge for its progressive economy and society. This paper aims to identify the future time periods in which the majority of the indices confirm Bangladesh as an aging country. This study estimates various demographic indices to reveal the age structural transition of Bangladesh's population for 2011-2061. Furthermore, it has computed general distribution indices, the aging index, the Billeter index as reproductive indices, and several economic and support dependency ratios. The trend line of the coefficients of inflow, outflow, and exchange of the productive population has been drawn in order to visualize the future workforce. It has been observed that Bangladesh will be an aging country between 2030 and 2035, taking into account major traditional measures of population aging. In this sense, it is a novel finding for policy implications to overcome the upcoming challenges of the inevitable population aging in Bangladesh. To deal with the implications and drivers of population ageing several steps are required to consider by the government and private institutions.International Journal of Statistical Sciences, Vol. 24(2), November, 2024, pp 109-124